Faktor yang Berpengaruh dalam Pelaksanaan Serah Terima menggunakan Teknik SBAR: Determinant Factors in the implementation of Handover using the SBAR Technique - Purwaningsih, Ika; Ratnasari; Yanto, Arief (Jurnal Keperawatan Sumba (JKS), 2025)
One form of communication between nurses is the handover, often conducted using the SBAR (Situation, Background, Assessment, Recommendation) method. Several factors, such as nurse knowledge, leadership, and colleague support, can influence the effectiveness of patient handovers. This study aims to identify the factors that influence the implementation of patient handovers using SBAR communication at SMC Telogorejo Hospital. The research design is associative-analytic, with a cross-sectional approach. The sample size was 119 respondents, selected using purposive sampling. The results showed that most respondents had good knowledge (52.1%), demonstrated good leadership (51.3%), received good peer support (52.1%), and conducted good handovers (59.7%). The study found that knowledge had no significant influence on the implementation of patient handovers using SBAR communication. However, leadership and peer support were significantly associated with the effectiveness of patient handovers using SBAR at SMC Telogorejo Hospital. The most influential factor was leadership, with a p-value of 0.000 (p < 0.05). Future research should incorporate additional factors related to the implementation of patient handovers using SBAR technique.